2016
DOI: 10.3892/ijo.2016.3439
|View full text |Cite
|
Sign up to set email alerts
|

Human rhabdomyosarcoma cells express functional pituitary and gonadal sex hormone receptors: Therapeutic implications

Abstract: Evidence has accumulated that sex hormones play an important role in several types of cancer. Because they are also involved in skeletal muscle development and regeneration, we were therefore interested in their potential involvement in the pathogenesis of human rhabdomyosarcoma (RMS), a skeletal muscle tumor. In the present study, we employed eight RMS cell lines (three fusion positive and five fusion negative RMS cell lines) and mRNA samples obtained from RMS patients. The expression of sex hormone receptors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 50 publications
0
11
0
1
Order By: Relevance
“…All hormones were prepared according to the manufacturer’s recommendations. Lyophilisates were dissolved in the substances recommended in the product specification [ 24 26 ] and based on previous experience [ 21 , 22 , 27 ] and then added to the culture medium:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All hormones were prepared according to the manufacturer’s recommendations. Lyophilisates were dissolved in the substances recommended in the product specification [ 24 26 ] and based on previous experience [ 21 , 22 , 27 ] and then added to the culture medium:…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, functional expression of FSH and LH receptors in established breast cancer cell lines has shown that sex hormones (SexHs) regulate breast cancer cell motility, adhesion, and invasion [ 20 ]. Moreover, functional receptors for pituitary gonadotropins and gonadal SexHs were identified on the surface of human lung cancer cells [ 16 ], rhabdomyosarcoma cells [ 21 ], and leukemia cells [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…RMS can be divided into two histological subtypes: embryonal rhabdomyosarcoma (ERMS) and alveolar rhabdomyosarcoma (ARMS). ARMS is associated with more aggressive behavior which has a worse prognosis than ERMS [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has accumulated that several types of malignancies share certain markers with germ cells and respond to stimulation by SexHs (1,46). In support of this connection, some tumors express pluripotency markers (e.g., Oct-4), secrete carcinoembryonic antigen (CEA), express cancer-testis antigens (CTAs), and respond by proliferation after stimulation by both pituitary and gonadal SexHs (2630).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has accumulated that sex hormones (SexHs) play a role in the development and progression of several malignancies arising in the gonads (1), urogenital tract (24), breast (5), skeletal muscles (6) and hemato/lymphohematopoietic tissues (7). Gonadal SexHs, and in particular pituitary SexHs such as follicle-stimulating hormone (FSH), luteinizing hormone (LH), and prolactin (PRL), are potent mitogens, and their enhanced level in peripheral blood (PB) is associated with prostate, colon, and lung cancer (8–11).…”
Section: Introductionmentioning
confidence: 99%